Synthesis of magnetic biochar from agricultural waste biomass to enhancing route for waste water and polymer application: A review - Thines, K.; Abdullah, E.; Mujawar, Mubarak; Ruthiraan, M. (Elsevier Science Ltd, 2017)
© 2016 Elsevier LtdThe development of magnetic biochar from biomass and the prospect of developing magnetic nanomaterials have attracted many researchers worldwide. The conversion of this biomass into something more prospective has reduced the waste management issue without any hassle. Magnetic biochar which is derived from various types of biomass exhibits a good magnetic property with high surface area and significant morphology through various production methods. These magnetic biochar showed a remarkable application as an adsorbent for various wastewater treatments and were cooperated in certain selected polymer composites for application in supercapacitor. This study provides an extensive summary of various production methods of magnetic biochar along with its application in wastewater treatment and selected polymer cooperation.